Strategies for post–cardiac surgery acute kidney injury prevention: A network meta-analysis of randomized controlled trials - Chen, Jia-Jin; Lee, Tao Han; Kuo, George; Huang, Yen-Ta; Chen, Pei-Rung; Chen, Shao-Wei; Yang, Huang-Yu; Hsu, Hsiang-Hao; Hsiao, Ching-Chung; Yang, Chia-Hung; Lee, Cheng-Chia; Chen, Yung-Chang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objects: Cardiac surgery is associated with acute kidney injury (AKI). However, the effects of various pharmacological and nonpharmacological strategies for AKI prevention have not been thoroughly investigated, and their effectiveness in preventing AKI-related adverse outcomes has not been systematically evaluated. Methods: Studies from PubMed, Embase, and Medline and registered trials from published through December 2021 that evaluated strategies for preventing post–cardiac surgery AKI were identified. The effectiveness of these strategies was assessed through a network meta-analysis (NMA). The secondary outcomes were prevention of dialysis-requiring AKI, mortality, ICU length of stay (LOS), and hospital LOS. The interventions were ranked using the P-score method. Confidence in the results of the NMA was assessed using the Confidence in NMA (CINeMA) framework. Results: A total of 161 trials (involving 46,619 participants) and 53 strategies were identified. Eight pharmacological strategies {natriuretic peptides [odds ratio (OR): 0.30, 95% confidence interval (CI): 0.19–0.47], nitroprusside [OR: 0.29, 95% CI: 0.12–0.68], fenoldopam [OR: 0.36, 95% CI: 0.17–0.76], tolvaptan [OR: 0.35, 95% CI: 0.14–0.90], N-acetyl cysteine with carvedilol [OR: 0.37, 95% CI: 0.16–0.85], dexmedetomidine [OR: 0.49, 95% CI: 0.32–0.76;], levosimendan [OR: 0.56, 95% CI: 0.37–0.84], and erythropoietin [OR: 0.62, 95% CI: 0.41–0.94]} and one nonpharmacological intervention (remote ischemic preconditioning, OR: 0.76, 95% CI: 0.63–0.92) were associated with a lower incidence of post–cardiac surgery AKI with moderate to low confidence. Among these nine strategies, five (fenoldopam, erythropoietin, natriuretic peptides, levosimendan, and remote ischemic preconditioning) were associated with a shorter ICU LOS, and two (natriuretic peptides [OR: 0.30, 95% CI: 0.15–0.60] and levosimendan [OR: 0.68, 95% CI: 0.49–0.95]) were associated with a lower incidence of dialysis-requiring AKI. Natriuretic peptides were also associated with a lower risk of mortality (OR: 0.50, 95% CI: 0.29–0.86). The results of a sensitivity analysis support the robustness and effectiveness of natriuretic peptides and dexmedetomidine. Conclusion: Nine potentially effective strategies were identified. Natriuretic peptide therapy was the most effective pharmacological strategy, and remote ischemic preconditioning was the only effective nonpharmacological strategy. Preventive strategies might also help prevent AKI-related adverse outcomes. Additional studies are required to explore the optimal dosages and protocols for potentially effective AKI prevention strategies.